PREPROCESSING OF THE KITSAT-1 CCD EARTH IMAGES - Impyeong Lee; Taejung Kim; Seorim Lee; Soon D. Choi (Journal of Astronomy and Space Sciences, 1996)
Thc CCD earth image experiment(CEIE) is one of the main payload of the KITSAT-1. Since it was launched on Age. 11, 1992, the CEIE has taken more than 500 images on the earth surface world-wide so far. An image from the space is very different from a feature on the real Earth surface due to various radiometric and geometric distortions. Preprocessing to remove those distortions has to take place before the image data are processed and analyzed further for various applications. This paper summarizes the result of the operation of the CEIE and describes the procedure to perform preprocessing including radiometric and geometric correction.